The impact of NH₄⁺ loading on the scleractinian coral Acropora - Fisher, Molly Ann (Kansas State University, 2022)
Coral reefs are one of the most diverse and complex ecosystems in the world supporting an estimated 25-38% of all marine life. Unfortunately, coral reef ecosystems and their keystone organisms, scleractinian coral, are declining at an alarming rate due to anthropogenic activities. Some species such as those within the genus Acropora, are imperative to reef ecosystems on a global scale; however, Acropora are considered to be the most sensitive to anthropogenic stressors. How these crucial reef builders respond to stressors such as bleaching and acidification is widely known; however, how Acropora respond to eutrophic conditions is greatly understudied in comparison as the ocean has historically been nitrogen (N) limited. Scleractinian coral rely upon associated microbes, Symbiodinium, and heterotrophic feeding to supplement their N demand. Under high N conditions, the balance between the coral and Symbiodinium is disrupted with uncontrollable Symbiodinium division and the retention of nutrient-rich photosynthates. The balance between metabolism (photosynthesis and respiration) and N cycling rates allow for a better understanding of coral physiological responses to environmental stressors. Here I am interested in determining how varying ammonium (NH₄⁺) levels impact 1.) metabolism measurements in aquacultured and wild Acropora and 2.) remineralization, nitrification, and uptake rates in aquacultured and wild Acropora and their surrounding environment. These experiments seek to improve the understanding of how scleractinian coral respond to eutrophic conditions, specifically NH₄⁺ loading. Surface area measurements of each Acropora fragment were required to properly scale metabolism and N cycling rates. Methods to determine surface area measurements are ubiquitous throughout scientific literature and the accuracy of these methods are often debated upon. Two of the most cost-effective and cited surface area methods are foil wrapping and wax dipping. Neither method produced statistically significant differences in the aquacultured Acropora surface area estimations and displayed similar results using calibrated objects. I determined the foil wrapping method best suited our study. Metabolism measurements conducted on scleractinian coral can estimate the energy produced and consumed by the coral and its associated Symbiodinium and microbes. I measured respiration and primary production in Acropora exposed to varying levels of NH₄⁺ under light and dark conditions. I found a significant, positive relationship between aquacultured Acropora primary production and the level of NH₄⁺ treatment; however, there was not a significant relationship between NH₄⁺ treatment levels and respiration in both the aquacultured and wild Acropora. Respiration rates were significantly different between wild Acropora fragments collected from two different sites surrounding the island of Guam. These findings indicate that factors other than NH₄⁺ influence respiration rates while primary production is limited by N. Rates of remineralization, nitrification, and uptake are not well established for corals and their associated microbial communities. However, these rates, similarly to metabolism rates, can determine how scleractinian coral respond to increasing levels of NH₄⁺. I quantified rates of remineralization, nitrification, and uptake for wild and aquacultured Acropora subjected to elevated NH₄⁺ treatments using an isotopic tracer method. Rates of remineralization, nitrification, and uptake in aquacultured and wild Acropora were not statistically different among NH₄⁺ treatment levels. Lastly, rates of remineralization, uptake, and nitrification of both aquacultured and wild Acropora under varying NH₄⁺ treatments are presented and compared to rates from previous studies. Acropora uptake and nitrification rates were consistent with rates presented in previous studies with scleractinian coral under ambient seawater. These rates of N cycling in Acropora are some of the first to be quantified for scleractinian coral under elevated NH₄⁺ treatments.
Keywords: Eutrophication; Nitrogen; Scleractinian coral; Metabolism; Nitrogen cycle; Guam